Construction dispute resolution handbook - Gaitskell, Robert; Gaitskell, Robert (ICE, 2011)
The "Construction Dispute Resolution Handbook" provides construction professionals and lawyers with straightforward and pragmatic advice on dealing with construction disputes, at all stages, using principles that are applicable internationally.
Previous ed.: published as Engineer's dispute resolution handbook. London: Thomas Telford, 2006.
Keywords: Engineers -- Malpractice -- England.; Engineers -- Malpractice -- Wales.; Dispute resolution (Law) -- England.; Dispute resolution (Law) -- Wales.; Engineering contracts -- England.; Engineering contracts -- Wales.; elektronické knihy; electronic books